Effect of the delay of the second foot on the total impulse in a vertical jump with run - M. Gutiérrez-Dávila; J. Campos; E. Navarro (Asociación Española de Ciencias del Deporte, 2010)
This paper aims to identify the influence that the delay of the second foot in a vertical jump with run up approach, has on the total impulse, impulse absorption, impulse acceleration, and on the percentage participation of each foot during the takeoff phase. Twenty three physical education undergraduates students participated in the study recruited among university basketball and volleyball players (mean height: 179 ± 6.1 cm; mean mass: 70.96 ± 8.82 kg). Two force platforms were used, one for each foot support (Dinascan - IBV) at 250 Hz frequency and time-synchronized to one another and to a high speed video camera (Redlake Motion Space 1000 S). Results showed that the lower the time between the first and second contact foot, the lesser the takeoff time (p<0.001), although this reduction is only attributed to the negative period. The impulse of acceleration was not affected by the delay of the second foot, so that there would not be advantages regarding jump height. There is a bigger reduction of the horizontal velocity when the time between the first and the second contact foot is increased (p<0.01).